2007
DOI: 10.1007/s00464-007-9670-5
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic repair of perforated duodenal ulcers: The simple “one-stitch” suture with omental patch technique

Abstract: This simple "one-stitch" suture with omental patch technique is a safe and easy procedure, and it has an acceptable morbidity rate and a low conversion rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 13 publications
2
30
0
1
Order By: Relevance
“…[2][3][4][5] However, the routine treatment for perforated peptic ulcer still seems to be by upper laparotomy, representing the main motive for reviewing the literature. [6] The introduction of proton pump inhibitors and H2 antagonists into clinical use together with the recognition of Helicobacter pylori have caused a dramatic improvement in the medical management of uncomplicated peptic ulcer.…”
Section: Resultsmentioning
confidence: 99%
“…[2][3][4][5] However, the routine treatment for perforated peptic ulcer still seems to be by upper laparotomy, representing the main motive for reviewing the literature. [6] The introduction of proton pump inhibitors and H2 antagonists into clinical use together with the recognition of Helicobacter pylori have caused a dramatic improvement in the medical management of uncomplicated peptic ulcer.…”
Section: Resultsmentioning
confidence: 99%
“…In that case, we inserted surgical gauzes between the liver bed and upper border of the duodenum to expose the operative field, and we tilted the operation table more vertically to secure an operative field. Various laparoscopic techniques have been designed to repair the perforated site and their usefulness has been evaluated [9,[12][13][14]. Since the edge of the perforation site is characterized by inflammation and friableness, a minor fissure of the repair site resulting from tight fastening might result in an unsatisfactory closure.…”
Section: Discussionmentioning
confidence: 99%
“…The laparoscopic surgery for duodenal perforation was started in the year 1990 (12). A systemic review of three randomized control study in 315 patient comparing the open and laparoscopic duodenal perforation repair suggested that operative time for the laparoscopic duodenal perforation repair is less than the open as contrary to the previous studies but this study failed to suggest difference in the abdominal septic complications, pulmonary complications, morbidity, mortality, and reoperation rate (15). A systemic review of 56 studies could not suggest the better technique between the two open and laparoscopy approach (16).…”
Section: Discussionmentioning
confidence: 63%